2020
DOI: 10.1177/1057083720926740
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Program Directors Concerning Design and Implementation of the Master of Music Degree in Music Education

Abstract: The key research question for this qualitative study was as follows: How do program directors in selected schools describe the successes and challenges related to the design of their Master of Music degree in music education? Data sources included website content for 21 NASM-accredited programs and individual interviews with program directors from seven institutions. Program directors outlined several challenges associated with program development, including how to address the practical needs of music teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The extent to which traditional academic year programs, hybrid, summer, and online programs vary in the research/teaching percentage allocation is unclear because many participants reported that their institution offers more than one delivery format (e.g., online program and academic year program). This varied allocation was also considered unclear by Conway et al’s (2020, 2021) participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent to which traditional academic year programs, hybrid, summer, and online programs vary in the research/teaching percentage allocation is unclear because many participants reported that their institution offers more than one delivery format (e.g., online program and academic year program). This varied allocation was also considered unclear by Conway et al’s (2020, 2021) participants.…”
Section: Discussionmentioning
confidence: 99%
“…In recent investigations, music education faculty have also provided perspectives on the function of the MME degree. Conway et al (2020, 2021) interviewed the program directors of seven MME programs. Those program directors in the 2020 study indicated a variety of challenges related to recruitment, enrollment, and funding of students; reputation of the program; state policy issues; the need for students to engage with empirical research and critical thinking to a greater extent; issues related to faculty time and student time commitments; and difficulty in defining success for the MME degree.…”
Section: Research and Pedagogy In Mme Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that program directors expressed a challenge in meeting the professional needs of MME students while also maintaining high instructional standards that are necessary to prepare students for doctoral study in the future. One of the program directors in their study characterized this challenge as teaching for “education versus vocational training” (Conway et al, 2020, p. 96).…”
mentioning
confidence: 99%
“…Fung (2004) recommended that "both traditional and flexible modes of learning" (p. 119) be used in graduate programs to increase accessibility to more students while also preserving some face-to-face instruction with faculty. Conway et al (2020) examined the content of 21 MME program websites and interviewed directors of seven MME programs, including academic year, online, summer, and hybrid degree formats. They reported that program directors expressed a challenge in meeting the professional needs of MME students while also maintaining high instructional standards that are necessary to prepare students for doctoral study in the future.…”
mentioning
confidence: 99%